(untitled) (Global Journal of Management and Business Research, 2015)
The purpose of this research is to examine the relationship between bank-specific and macro-economic indicator over bank performance by using data of ten Pakistani banks including five conventional banks and five Islamic banks over the period 2010-2014. Dependent variable taken for this study is Return on assets, Return on Equity to measure the Banking Sector Performance and independent variable taken for this study including specific factors (Size, Capital, Loan, Deposits, Expenses, Credit Risk and Liquidity) and macroeconomic factors (Gross Domestic Product, Foreign Direct investment and Inflation).This paper uses the correlation and regression method to investigate the impact of size, loans, capital, deposits, liquidity, credit risk, expenses, economic growth, inflation and foreign direct investment on major performance indicators. The empirical results have found strong evidence that both internal and external factors have a strong influence on the performance. A result of study denotes that credit risk, expenses and inflation have indirect link with the bank performance, whereas size of bank, capital, deposit and loan have a significant positive relation with bank’s performance and liquidity have insignificant positive relation with Performance of bank. This study reveals the positive insignificant relation between GDP and performance but significant relation between FDI and performance and indirect relation between inflation and profitability. The results of the study are of value to both academics and policy makers.